PROSES AFIKSASI PADA INKORPORASI PELESAPAN VERBA DALAM BAHASA BALI - Made Detrichyeni Winaya; I Gusti Ngurah Adi Rajistha (Universitas Warmadewa, 2017)
[Title: The Affixation Process in Verb Incorporation in Balinese Language] The incorporation of verbs in Balinese language requires the morphological process of the word that will replace the verb position. The incorporation process in Balinese is usually followed by affixation process. This article aims to explain the affixation process of incorporating verbs in Balinese language. The source of data of this research is a modern Balinese story book titled Tutur Bali by I Wayan Westa (2013). The data of this research is obtained through library method with technique of note. The data obtained were classified according to the type of affixation that occurs. The classified data were analyzed using the distributional method. The result of analysis is presented by informal method. Based on the analysis that has been conducted, the affixation process found in the case of incorporation of verbs involves the process of prefixation, the process of suffixation, and the process of adding the affix combination. The prefixing process involves the addition of ma- and N-. Furthermore, the process of suffixation includes the addition of the suffix -in. The last morphological process is the addition of a combination of affixes such as N-in, N-ang, ma-an, ma-in, ka-in, -ang-a, and -in-a.